‘Nature positive’ must incorporate, not undermine, the mitigation hierarchy - Maron, M; Quétier, F; Sarmiento, M; ten Kate, K; Evans, MC; Bull, JW; Jones, JPG; Zu Ermgassen, SOSE; Milner-Gulland, EJ; Brownlie, S; Treweek, J; von Hase, A (Springer Nature, 2023)
For the concept of nature positive to succeed as the lodestar for international action on biodiversity conservation, it must build upon lessons learned from the application of the mitigation hierarchy — or risk becoming mere greenwash.